Toward a Taylor rule for fiscal policy - Martin Kliem; Alexander Kriwoluzky (Deutsche Bundesbank, 2010)
This paper presents a procedure to determine policy feedback rules in dynamic stochastic general equilibrium (DSGE) models. We illustrate our approach with fiscal feedback rules for tax instruments in a standard medium-scale DSGE model. First, we approximate the optimal dynamic behavior of the economy using simple linear feedback rules. Then we calculate the elasticities of the model variables' moments with respect to the feedback coefficients. The feedback coefficients associated with the highest elasticities form the policy feedback rules to be estimated. Our results stress the importance of carefully modeled fiscal tax policy in two dimensions: (i) with respect to the dynamic responses of fiscal policy to exogenous shocks and (ii) with respect to the historical shock decomposition of fiscal policy.
Keywords: E62; H30; C51; 330; Fiscal policy; Bayesian model estimation; Identification